Examining the Impact of Sensory Marketing on Young Consumers: A McDonald’s Case Study - Mbatha, Vusumuzi David; Koopman, Aaron; Chuchu, Tinashe (International Review of Management and Marketing, 2023)
In recent years research on sensory marketing has attracted the attention of marketing researchers and scholars alike. The purpose of this study is to investigate the impact of sensory stimuli that is used to create arousal, and to examine whether this arousal influences consumer attitudes and purchase intentions. Previously documented literature was used as a foundation for this research while additional opportunities to expand this topic’s literature was identified. While previous studies and results on sensory marketing exist, there is a lack of South African related literature on the concept. The quantitative research approach was used to measure the proposed conceptual model and hypotheses, and the convenience sampling method was chosen as the technique to acquire the required sample. To facilitate this study, a seven-point Likert scale was used with questions and statements adapted from previous literature. Of the 300 distributed surveys, 279 were returned, deemed viable, processed and interpreted. The findings of this study support all the proposed hypotheses. Furthermore, this study’s findings and conclusions contribute towards comprehension of sensory marketing from a young consumer’s perspective.